2019
DOI: 10.1177/2054358119879451
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Patient Reported Outcomes in Clinical Nephrology Practice: A Qualitative Pilot Study

Abstract: Background: Use of patient-reported outcome measures (PROM) in clinical practice can offer clinicians important information about the impact of illness on patients and their quality of life. Electronic reporting of patient-reported outcomes (ePROs) provide quick access of this information to the health care team. Although this type of information is acknowledged to be critical to not only improving the quality of care but also involving patients in care planning, little is known about how ePRO reports can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The use of the ESAS‐r has been reported to improve patient‐focused assessment and facilitate monitoring of symptoms and taking management actions in patients on dialysis . PROMs such as the ESAS‐r are central to patient‐centered care as they harness the patient voice and perspectives and improve patient‐clinician communication .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the ESAS‐r has been reported to improve patient‐focused assessment and facilitate monitoring of symptoms and taking management actions in patients on dialysis . PROMs such as the ESAS‐r are central to patient‐centered care as they harness the patient voice and perspectives and improve patient‐clinician communication .…”
Section: Discussionmentioning
confidence: 99%
“…Since the ESAS‐r is used among patients on dialysis in multiple jurisdictions, it may provide the opportunity for longitudinal follow‐up of symptoms in patients with various stages of chronic kidney disease (CKD), improving continuity of care . The use of the ESAS‐r in clinical care may improve patient–physician communication, may facilitate better understanding of underlying medical or psychosocial factors potentially linked to symptom experience, and may help identify patients who benefit from additional assessment or support . If validity and utility is confirmed, the ESAS‐r could also be used in clinical studies to follow patients with ESKD through various stages of the CKD trajectory and allow clinicians to develop a better understanding of the evolution of their symptom burden.…”
Section: Introductionmentioning
confidence: 99%
“… 81 The use of ePROMs in the management of patients receiving home dialysis is also being trialled in the ePRO Kidney study. 82 …”
Section: Ongoing Eprom Initiativesmentioning
confidence: 99%
“…However, there was no significant difference measured for HRQOL or improvement in home dialysis care [19]. Another study examining the use of electronic PROs in patients receiving home dialysis care found that electronic PROs were useful for obtaining information that allowed for better person-centered care and clinicians asked more questions about symptoms and were more involved [9]. However, the study was unable to determine whether the intervention would be better than usual care, necessitating more research in this area.…”
Section: Integration Of the Patient Perspective With Technologymentioning
confidence: 99%
“…There are not enough strategies to assist health-care providers in the use of PRO measures when evaluating kidney care. One approach aims to address PROs with the use of a realist synthesis approach, looking at a wide range of data, to create a kidney-specific program theory to optimize the use of PROs on individual and aggregate levels of patient-centered care [9]. There has also been a push toward collecting PROs electronically directly from the patients, and now, with a push toward telemedicine because of the COVID-19 pandemic, EHRs may become the best mode of communication between physician and patient.…”
Section: Measurement Of Pro In Patients With Kidney Diseasementioning
confidence: 99%